Financial statement ratio analysis to assess the performance of PT Adaro minerals Indonesia TBK and its subsidiaries - Stivaniyanti Atmanegara; Habibullah Arief; Emha Diambang Ramadhany; Aurelia Reyza Safitri Husaini; Rieke Fenita Lorenza; Mahendra, I Dewa Made Yuda (Jurnal Ekonomi, 2024)
PT Adaro Minerals Indonesia Tbk (IDX: ADMR) is a subsidiary of PT Adaro Energy Indonesia Tbk that focuses on coal mining, metallurgy and mineral processing. The company currently operates as the first and only metallurgical coal producer in Indonesia and is building an aluminum smelter in a green industrial estate in North Kalimantan.The company is also preparing to commence mineral processing operations as part of Adaro's transformation towards a green business. In 2022, his subsidiary company, PT Kalimantan Aluminium Industry, started the pre-construction phase of an aluminum smelter in the world's largest green industrial area located in North Kalimantan. In the initial phase, the project is expected to produce around 500,000 tons/year of aluminum ingots, which will be increased to 1.5 million tons/year at full scale. Mineral processing is the company's effort to contribute while capturing green economy opportunities that are intensively developed by the government. The company has internal and external financial statements. In this case, the company can use ratio analysis to financial statements. Meanwhile, the data method used in this study uses observation methods and literature studies related to PT Adaro Minerals Indonesia's financial data, to then be analyzed by calculating arithmetic ratios that can be interpreted in economic relations related to company performance. The results of financial statement analysis use measurements of Liquidity Ratio, Leverage Ratio, Activity Ratio, Profitability Ratio, and the company has sufficient ability to take action in guaranteeing and paying off debts to creditors, and for the results of other business financial ratio analysis can be done. Used as a benchmark for investors in investing funds into the company.